Development of the Kids Incubator Financial Literacy Program Towards Future-Ready Leaders: A Conceptual Program - Alifah, Khairunnisa Zulfa; Ekasari, Lintang Analisa; Wibowo, Setiawan Edi (Jurnal Pendidikan Progresif, 2024)
Development of Kids Incubator Financial Literacy Program Towards Future-Ready Leaders : A Conceptual Program. Objective : This study aims to enhance financial literacy skills in students through the development of a Financial Literacy Incubator program. Financial literacy is crucial for students to make informed decisions about managing money, saving, investing, and understanding the basic principles of economics. However, current education systems often lack effective tools to teach these skills. The study addresses this gap by developing a Financial Literacy Incubator program that integrates interactive learning tools and technology to engage students in understanding financial concepts such as budgeting, saving, investing, and financial planning. Methods: The development of the program follows the PLOMP model, which includes phases of preliminary research, prototyping, and evaluation to ensure the program's validity and practicality. The program was tested with a group of students from SD Muhammadiyah Al Mujahidin, with feedback gathered from teachers and students through surveys and interviews. Findings: The results indicate that the Financial Literacy Incubator program is both valid and practical for use in elementary education, significantly enhancing students' understanding of basic financial principles and improving their financial decision-making skills. Conclusion : The study concludes that integrating interactive and technology-based tools into financial literacy education can effectively support the development of essential financial skills. Keywords : financial literacy, financial incubator, interactive learning, elementary education, technology integration.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024127